Multi-omics analysis provides insights into lignocellulosic biomass degradation by Laetiporus sulphureus ATCC 52600 - de Figueiredo, Fernanda Lopes; de Oliveira, Ana Carolina Piva; Terrasan, Cesar Rafael Fanchini; Gonçalves, Thiago Augusto; Gerhardt, Jaqueline Aline; Tomazetto, Geizecler; Persinoti, Gabriela Felix; Rubio, Marcelo Ventura; Peña, Jennifer Andrea Tamayo; Araújo, Michelle Fernandes; de Carvalho Silvello, Maria Augusta; Franco, Telma Teixeira; et al. (Springer Nature, 2021)
Background: Wood-decay basidiomycetes are effective for the degradation of highly lignified and recalcitrant plant substrates. The degradation of lignocellulosic materials by brown-rot strains is carried out by carbohydrate-active enzymes and non-enzymatic Fenton mechanism. Differences in the lignocellulose catabolism among closely related brown rots are not completely understood. Here, a multi-omics approach provided a global understanding of the strategies employed by L. sulphureus ATCC 52600 for lignocellulose degradation. Results: The genome of Laetiporus sulphureus ATCC 52600 was sequenced and phylogenomic analysis supported monophyletic clades for the Order Polyporales and classification of this species within the family Laetiporaceae. Additionally, the plasticity of its metabolism was revealed in growth analysis on mono- and disaccharides, and polysaccharides such as cellulose, hemicelluloses, and polygalacturonic acid. The response of this fungus to the presence of lignocellulosic substrates was analyzed by transcriptomics and proteomics and evidenced the occurrence of an integrated oxidative–hydrolytic metabolism. The transcriptomic profile in response to a short cultivation period on sugarcane bagasse revealed 125 upregulated transcripts, which included CAZymes (redox enzymes and hemicellulases) as well as non-CAZy redox enzymes and genes related to the synthesis of low-molecular-weight compounds. The exoproteome produced in response to extended cultivation time on Avicel, and steam-exploded sugarcane bagasse, sugarcane straw, and Eucalyptus revealed 112 proteins. Contrasting with the mainly oxidative profile observed in the transcriptome, the secretomes showed a diverse hydrolytic repertoire including constitutive cellulases and hemicellulases, in addition to 19 upregulated CAZymes. The secretome induced for 7 days on sugarcane bagasse, representative of the late response, was applied in the saccharification of hydrothermally pretreated grass (sugarcane straw) and softwood (pine) by supplementing a commercial cocktail. Conclusion: This study shows the singularity of L. sulphureus ATCC 52600 compared to other Polyporales brown rots, regarding the presence of cellobiohydrolase and peroxidase class II. The multi-omics analysis reinforces the oxidative–hydrolytic metabolism involved in lignocellulose deconstruction, providing insights into the overall mechanisms as well as specific proteins of each step.
Keywords: Basidiomycetes; Brown-rot; CAZymes; Fenton reaction; Genome; Proteome; Sugarcane by-products; Transcriptome